Ecstatic émigré : an ethics of practice - Keelan, Claudia, 1959- (Ann Arbor : University of Michigan Press, 2018)
"Most think of an emigré as one who leaves her native land to find home in another. Claudia Keelan, in essays both personal and critical, enlists poetic company for her journey, engaging both canonical and common figures, from Gertrude Stein to a prophetic Las Vegas cab driver named Caesar. Mapping her own peripatetic evolution in poetry and her nomadic life, she also engages with Christian and Buddhist doctrines on the virtues of dispossession. Ecstatic Émigré pays homage to poets from Thoreau and Whitman to Alice Notley, all of whom share a commitment to living and writing in the moment. Keelan asks the same questions about the growth of flowers or the meaning of bioluminescence as she does about the poetics of John Cage or George Oppen. Her originality is grounded by the ways in which she connects poetic principles with the spiritual concepts of via negativa demonstrated both in St. John of the Cross and Mahayana Buddhism. In addition, her essays demonstrate an activist spirit and share a commitment to the passive resistance demonstrated in Martin Luther King, Jr.'s concept of the "beloved community" and philosopher Simone Weil's dedication to "exile.""--
Prologue: reading and writing spiritual utility -- Preliminaries -- Apology -- A concrete memoir -- From Without sovereignty -- "It might have begun differently" -- Revising the parade : against the poetry of witness -- Reclaiming paradise -- A hinge-history : Robinson Jeffers and Brenda Hillman -- A garden is a frame structure -- From Erasing names, multiplying alliances (Salt Lake City via Memphis via Las Vegas) -- Snow in America (Boston) -- Nearing cradle -- Native stranger -- Lessons of the whirlwind -- The citizen stranger : an ethics of definition -- The instant -- Interview for The Range of the Possible, conducted by Tod Marshall (The Secularist and Utopic) -- Interview for Barrow Street, conducted by Derek Pollard (Utopic and The Devotion Field) -- The poet on the poem : For My Lost Original : Elegy Is a Seeking in "Everybody's Autobiography" (Missing Her) -- Interview for Omnidawn Press, conducted by Rusty Morrison (Truth of My Songs : Poems of the Trobairitz) -- Poetics statement for Poetry Society of America, "In their own words" (O, Heart) -- Interview with Thomas Barkman for Barrow Street (O, Heart).
Includes bibliographical references (pages 165-168).
Print version record.
JSTOR
Keywords: Poetics; Poetry -- Authorship; American poetry -- History and criticism; Poétique.; Poésie -- Art d'écrire.; Poésie américaine -- Histoire et critique; POETRY -- General; LITERARY CRITICISM -- Poetry; American essays; Poetry; American poetry; Poetics; Poetry -- Authorship; 2000-2099; Criticism, interpretation, etc